PENGARUH BEBAN KERJA DAN KOMITMEN TERHADAP KINERJA DAN KEPUASAN KERJA PERAWAT SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT TABRANI RAB PEKANBARU - Amalia, Lia; Marnis, Marnis; ningsih, dewita suryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the workload and commitment of nurses either directly or indirectly on performance and job satisfaction. This study used nurse population as a sample by using census method, because the sample for our data analysis is limited. Researchers applied the path technique using spss 21.0.The results of this study shows the workload has a significant positiv effect on performance, nurse commitment has a significant positive effect on performance, work load has a significant positive effect on job satisfaction and nurses commitment has a significant postive effect on job satisfaction and job satisfaction have a significant positive effect on the performance at hospital nurse tabrani rab pekanbaru.Keywords : Workload, Nurse Commitment, Performance and Job Satisfaction.